Waste To Wealth: Inovasi Eco-Craft Sebagai Solusi Berkelanjutan - Rahmaningtyas, Wisudani; Purasani, Hana Netti; Mudrikah, Saringatun; Oktavia, Citra Hansen; Dewi, Luthfiani Puspita; Safira, Mei Arum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Plastic waste presents a highly serious problem due to its extensive contribution to environmental pollution. According to data obtained from the Ministry of Environment and Forestry (KLHK), the state of waste management in Indonesia in 2023 shows alarming figures, with total waste reaching 68.5 million tons. Of this amount, approximately 17%, or around 11.6 million tons, is plastic waste. This reflects the difficulty in designing and implementing effective policies to manage and reduce the volume of waste generated nationwide. The low recycling rate is a key concern, with only 7% of the total waste entering Final Disposal Sites (TPA) successfully recycled. Field findings indicate that the volume of waste transported over the past three years, from 2020 to 2024, has increased annually. In 2024, it even rose from the previous year, increasing from 280,859 m³ to 300,566 m³. This data is further supported by the fact that the proportion of plastic waste is also significantly higher compared to other types of waste, standing at around 19%, whereas other waste categories are only in the range of 4–10%. In addition, based on data from the local Environmental Agency, West Ungaran District, with its daily activities, generates up to 500 m³ of waste per day, a figure far higher than Ambarawa District, which produces only 217 m³ per day. Survey results also show that public knowledge about eco-crafts remains low, at only 84.2%. In response to this situation, outreach activities and skills development in the utilization of plastic waste should become the main focus to address the problem. The approach of lectures, practical sessions, mentoring, monitoring, and evaluation is considered appropriate for designing training to address the issues in Nyatnyono, West Ungaran. The community service activity proceeded according to plan, and evaluation results indicated an improvement in the knowledge and skills of the participants. The follow-up for the next community service program will include training on branding, marketing, and selling.